The association of circulating prepartum metabolites, minerals, cytokines and hormones with postpartum health status in dairy cattle. (June 2020) - Macmillan, K.; Gobikrushanth, M.; Behrouzi, A.; López-Helguera, I.; Cook, N.; Hoff, B.; Colazo, M.G.
Abstract: The objectives were to evaluate differences in circulating prepartum metabolites, minerals, cytokines and hormones based on postpartum disease category and determine critical circulating concentrations of prepartum analytes associated with postpartum disease in 229 cattle from 11 commercial dairies in Alberta, Canada. Blood was collected at 8.8 ± 2.1 d prepartum and analyzed for a wide array of analytes. Cattle were categorized as healthy ( n  = 76) or as having inflammatory (INF; n  = 28), metabolic (MET; n  = 34) or inflammatory and metabolic (INFMET; n  = 91) postpartum diseases. The prepartum circulating concentrations of Cu were lesser (0.84 vs. 0.90 μg/mL; P  = 0.02) and concentrations of Mo (19.1 vs. 16.5 ng/mL; P  = 0.04) and NEFA (0.27 vs. 0.18 mmol/L; P  = 0.01) were greater in INFMET cattle compared with healthy cattle. The critical threshold for Cu, Mo and NEFA prepartum concentration that predicted INFMET was ≤ 0.81 μg/mL (sensitivity 45.5% and specificity 74.3%), ≥ 9.91 ng/mL (sensitivity 70.0% and specificity 52.7%) and ≥ 0.19 mmol/L (sensitivity 62.2% and specificity 79.7%), respectively. Regardless of differences in the prepartum circulating concentrations of Cu, Mo and NEFA among healthy cattle and those with postpartum disease, the use of these analytes to predict the incidence of postpartum diseases was limited. Highlights: In early lactation, 67% of dairy cattle were diagnosed with inflammatory and metabolic diseases, or both. Prepartum circulating concentrations of Cu were lesser in cattle with both diseases Prepartum concentrations of Mo and NEFA were greater in cattle with both diseases However, the use of prepartum analytes to predict postpartum diseases were limited